EFFECT OF BENZIMIDAZOL ON THE VIABILITY DEVELOPMENT AND SIZES OF ECHINOCOCCUS GRANULOSUS PROTOSCOLICIES IN MICE - Abdul jabber Rasmi (Basrah Journal of Veterinary Research)
This study was designed on to show the effect of albendazol and mebendazol alon and their combination on surviral , development and size of Echinococcus granulosus protoscolicies of (10 mg/ml) intraperitoneal in mice. The study show that the mebendazol and combination drugs were greater than the albendzol during on the first four days nor effect on the five day in vivo intraperitoneal administration of combination drugs were greater than albendazol and mebendazol alone on the development and size of cysts which about (5.2±2.17) , (7.0±1.0) , (10.0±3.16) for the development and (1.13±0.38) , (1.18±0.54) , (1.20±0.49) for the ysts size.